2013
DOI: 10.1038/srep03042
|View full text |Cite
|
Sign up to set email alerts
|

JAK1 truncating mutations in gynecologic cancer define new role of cancer-associated protein tyrosine kinase aberrations

Abstract: Cancer-associated protein tyrosine kinase (PTK) mutations usually are gain-of-function (GOF) mutations that drive tumor growth and metastasis. We have found 50 JAK1 truncating mutations in 36 of 635 gynecologic tumors in the Total Cancer Care® (TCC®) tumor bank. Among cancer cell lines containing JAK1 truncating mutations in the Cancer Cell Line Encyclopedia databank, 68% are gynecologic cancer cells. Within JAK1 the K142, P430, and K860 frame-shift mutations were identified as hot spot mutation sites. Sanger … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
61
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(69 citation statements)
references
References 29 publications
(42 reference statements)
5
61
1
Order By: Relevance
“…showed that JAK1 inhibition is associated with cell cycle arrest and apoptosis in colorectal cancer [25]. No effect on cell viability upon IFNγ was found in JAK1 mutant gynecological cell lines [10]. In conclusion, we confirmed the remarkably high frequency of JAK1 mutations and associations with impaired upregulation of antigen presenting machinery components in MSI endometrial cancers, which suggest a functional role for JAK1 in an intriguing tissue-specific manner.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…showed that JAK1 inhibition is associated with cell cycle arrest and apoptosis in colorectal cancer [25]. No effect on cell viability upon IFNγ was found in JAK1 mutant gynecological cell lines [10]. In conclusion, we confirmed the remarkably high frequency of JAK1 mutations and associations with impaired upregulation of antigen presenting machinery components in MSI endometrial cancers, which suggest a functional role for JAK1 in an intriguing tissue-specific manner.…”
Section: Discussionsupporting
confidence: 73%
“…Both studies also showed that JAK1 frameshift mutations in MSI tumors are tissue specific and significantly less important in colorectal cancers as compared with endometrial cancers. Similarly, Ren et al identified JAK1 frameshift mutations mainly in gynecological cancers, primarily in endometrial and cervical cancer, when sequencing more than 3,000 tumors from various human tissues [10]. Altogether, the occurrence of JAK1 mutation specifically in endometrial cancer is suggestive of a positive selection for this mutation in endometrial cancer.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Gab1 was immunoprecipitated using Gab1 mouse antibody. Immunoblotting was performed as described previously [6, 30-32]. …”
Section: Methodsmentioning
confidence: 99%